Replacing fishmeal with salmon hydrolysate reduces the expression of intestinal inflammatory markers and modulates the gut microbiota in Atlantic salmon (Salmo salar) - Sandbakken, Ingrid Schafroth; Su, Hang; Johansen, Louise; Zhang, Yupeng; Ringø, Einar; Røsbak, Randi; Yakovlev, Igor; Five, Kathrine Kjos; Olsen, Rolf Erik (Frontiers in Marine Science, 2024)
The feed legislation allows the use of fish protein hydrolysates in feed for the same species in which it came from, since enzymatic hydrolysis degrades the proteins and eliminates potential prions, which have caused disease in mammals, but not in fish. In this trial, we investigated the effects of partially replacing dietary fishmeal (FM) with salmon protein hydrolysate (FPH) on the intestinal gene expression and microbiota. Atlantic salmon post smolts were either fed a control diet containing 30% fishmeal (FM), a 20% FM diet with 9% salmon hydrolysate (FPH-09) or a 10% FM diet with 18% salmon hydrolysate (FPH-18), until doubling of weight. Gene expression analysis by RNA sequencing of pyloric caeca (PC), midgut (MG) and hindgut (HG) revealed a downregulation of immunological genes involved in inflammation in the intestine of FPH-18 fed salmon compared to salmon fed the FM control. The gene expression of paralogous peptide transporters (PepT) was analyzed by real time quantitative PCR in PC, anterior midgut (AMG), posterior midgut (PMG) and HG of salmon fed all the three diets. The PepT1b paralog had highest relative expression levels in PC and AMG, suggesting that PepT1b is most important for peptide uptake in the anterior intestine. PepT1a was also mainly expressed in the PC and AMG, but at lower levels than PepT1b and PepT2b in the AMG. The PepT2b paralog had high levels of expression in AMG, PMG and HG indicating that it contributed significantly to peptide uptake in the posterior part of the gastrointestinal tract. The gut microbiota in the mucosa and digesta of the MG and HG, were dominated by the phyla Cyanobacteria and Proteobacteria, but also Firmicutes were present. The only dietary effect on the microbiota was the higher prevalence of the phyla Spirochaetes in the mucosa of FPH-18 fed salmon compared to the FM fed salmon. In conclusion, replacing FM with salmon hydrolysate reduced the expression of inflammatory markers in the Atlantic salmon intestine suggesting improved health benefits. The reduced inflammation may be related to the reduced FM content, potentially bioactive peptides in the hydrolysate and/or the altered gut microbial composition.